Subaqueous geomorphology: options, tasks, needs - Rudowski, Stanisław; Wróblewski, Radosław; Dworniczak, Janusz; Szefler, Kazimierz; Hac, Benedykt; Gajewski, Łukasz (Bulletin of Geography. Physical Geography Series, 2019)
The purpose of the paper is to present the potentialities of current non-invasive methods for bottom surveys, including cartometric presentation of its relief and structure in both marine and inland reservoirs. The paper presents examples of results obtained in the Maritime Institute in Gdańsk during surveys carried out at the bottom of seas, lakes and rivers with the use of the same apparatus: primarily, a multibeam echosounder (MBES) to obtain a digital terrain model (DTM); a side-scan sonar (SSS) to obtain a general image of the nature of the bottom (its “roughness”); and seismic profiling (sub-bottom profiler, sediment echo sounder [SES]) to recognise the structure of the bottom. The obtained results constitute a necessary basis for carrying out further specialist surveys (non-invasive or invasive) when needed. Current bottom survey options that use MBES, SSS and SES may be treated as subaqueous equivalents of the subaerial potentialities of a land surface survey using LiDaR and GPR (Ground Penetration Radar).